The Effect of Neem Seed Oil (Azadirachta indica) and Clove Leaf Oil (Syzygium aromaticum) Mixture on Cabbage Head Caterpillars (Crocidolomia pavonana) - Utami Dwi Ginasti; Danar Dono; Toto Sunarto (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2020)
Crocidolomia pavonana is one of the important pest in Brassicaceae family. The used of botanical pesticides such as neem and clove can be used as alternative control for C. pavonana. This study aimed to examine the effect of neem oil, clove oil, and its mixture to C. pavonana. This experiment was conducted from November 2019 to May 2020 at the Laboratory Pesticides and Environmental Toxicology of the Department of Plant Pests and Diseases of the Faculty of Agriculture, Universitas Padjadjaran. The experimental method used in this research was Randomized Block Design with 21 treatments, i.e control, neem oil, clove oil, and its mixture at concentrations of 0,1%, 0,25%, 0,5%, and 1%, each treatments was replicated 3 times. The result of this experiment showed that single or mixed treatments (Neem : Clove) at consentration of 1% caused 100% larvae mortality. Mixed treatment at ratio 1:1 could inhibits the formation of pupa and imago, and could prolong the development time of larvae in instar II-III and instar II-IV. In addition, mixed treatment at ratio 2:1 was also prolong the development time of larvae in instar II-pupa, reduce food consumption, inhibit the formation of imago, and reduce the number of eggs C. pavonana.